A whole‐ecosystem method for experimentally suppressing ants on a small scale. Issue 4 (21st February 2022) - Hood, Amelia S. C.; Aryawan, Anak Agung Ketut; Advento, Andreas D.; Suberkah, Wahyu R.; Ashton‐Butt, Adham; Ps, Sudharto; Caliman, Jean‐Pierre; Naim, Mohammad; Foster, William A.; Turner, Edgar C.
Abstract: Ant suppression experiments have emerged as a powerful method for assessing the role of ants in ecosystems. However, traditional methods have been limited to canopy ants, and not assessed the role of ants on and below ground. Recent advances have enabled whole‐ecosystem ant suppression in large plots, but large‐scale experiments are not always feasible. Here, we develop a small‐scale, whole‐ecosystem suppression method. We compare techniques for monitoring suppression experiments, and assess whether habitat complexity in oil palm influences our method's effectiveness. We conducted ant suppression experiments in oil palm agroforestry in Sumatra, Indonesia. We used targeted poison baits, a physical barrier and canopy isolation to suppress ants in 4 m radius arenas around single palms. We sequentially tested three suppression methods that increased in intensity over 18 months. We sampled ant abundance before and after suppression by fogging, using pitfall traps and extracting soil monoliths. We also monitored ants throughout the experiment by baiting. We tested the soil for residual poison and monitored other invertebrates (Araneae, Coleoptera, Orthoptera and Chilopoda) to test for cross‐contamination. Plots were established under four oil palm management treatments that varied in their habitat complexity: reduced, intermediate and high understorey complexity treatments in mature plantation, and a recently replanted plantation. Post‐treatment ant abundance was 92% lower in suppression than control plots. Only the most intensive suppression method, which ran for the final 9 months, worked. Baiting rarely reflected the other monitoring methods. The treatment negatively affected Orthoptera, but not other taxa. There was no residual poison in the soil. Coleoptera abundance increased in suppression plots post‐treatment, potentially due to reduced competition with ants. Our findings were consistent across management treatments. We developed a whole‐ecosystem method for suppressing ants on a small scale in oil palm plantations. Our method represents a significant advance; previous reductions in ant abundance have not exceeded 38%. We provide the first example of ants being experimentally suppressed belowground. Baiting alone is not adequate for assessing suppression effectiveness, and testing a range of taxa for confounding impacts is important. Our study can act as a blueprint for developing suppression methods for other taxa, which offer unique insights into community ecology. Abstrak: Percobaan eksklusi semut adalah metode yang ampuh untuk menilai peran semut dalam ekosistem. Namun, metode tradisional terbatas untuk semut kanopi, dan tidak menilai peran semut di dalam dan di bawah tanah. Percobaan eksklusi semut dalam plot besar yang mencakup seluruh ekosistem telah dapat dilakukan, tetapi tidak selalu berhasil untuk percobaan skala besar. Di sini, kami mengembangkan metode eksklusi skala kecil yang meliputi seluruh ekosistem. Kami membandingkan teknik untuk memantau percobaan eksklusi, dan menilai apakah kompleksitas habitat di kelapa sawit memengaruhi efektivitas metode kami. Kami melakukan percobaan eksklusi semut di agroforestri kelapa sawit di Sumatera, Indonesia. Kami menggunakan umpan racun yang ditargetkan, penghalang fisik, dan isolasi kanopi untuk mengeksklusi semut di arena dengan radius 4 m yang mengelilingi tiap individu kelapa sawit. Secara berurutan, kami menguji tiga metode eksklusi yang meningkat intensitasnya selama 18 bulan. Kami mengambil sampel kelimpahan semut sebelum dan sesudah eksklusi dengan fogging, menggunakan perangkap pitfall, dan mengekstraksi monolit tanah. Kami juga memantau semut selama percobaan dengan memberi umpan. Kami menguji tanah untuk sisa racun dan memantau invertebrata lain (Araneae, Coleoptera, Orthoptera, dan Chilopoda) untuk menguji kontaminasi silang. Plot dibuat dengan empat perlakuan pengelolaan kelapa sawit yang kompleksitas habitatnya bervariasi: kompleksitas vegetasi lantai yang rendah, menengah, dan tinggi, di perkebunan yang berisi tanaman dewasa dan yang baru ditanami kembali. Kelimpahan semut pasca perlakuan adalah 92% lebih rendah dalam eksklusi daripada plot kontrol. Hanya metode eksklusi yang paling intensif, yang berjalan selama sembilan bulan terakhir, yang berhasil. Umpan jarang mencerminkan hasil dari metode pemantauan lainnya. Perlakuan tersebut berdampak negatif pada Orthoptera, tetapi tidak pada taksa lainnya. Kami mendeteksi tidak ada sisa racun di dalam tanah. Kelimpahan Coleoptera meningkat di plot eksklusi pasca perlakuan, kemungkinan karena berkurangnya persaingan dengan semut. Temuan kami konsisten di seluruh perlakuan manajemen. Kami mengembangkan metode eksklusi semut yang meliputi seluruh ekosistem untuk skala kecil di perkebunan kelapa sawit. Metode kami merupakan kemajuan yang signifikan; pengurangan kelimpahan semut tidak melebihi 38%. Kami memberikan contoh pertama percobaan eksklusi semut di bawah tanah. Umpan tidak memadai untuk menilai efektivitas eksklusi, dan penting untuk menguji berbagai taksa untuk memeriksa faktor pengganggu. Studi kami adalah cetak biru untuk mengembangkan metode eksklusi untuk taksa lain, yang menawarkan wawasan unik tentang ekologi komunitas.